2012
DOI: 10.1177/0954407012440937
|View full text |Cite
|
Sign up to set email alerts
|

Effects of engine operating parameters on diesel low-temperature combustion with split fuel injection

Abstract: This paper shows that a split-fuel-injection strategy can achieve robust, near-zero smoke and nitrogen oxide emissions at reduced exhaust gas recirculation levels under low-temperature combustion conditions. The overall objective of the work was to investigate the sensitivity (in terms of the engine emissions and the fuel economy) of a 50:50 (by mass) split-injection strategy to variations in the key engine operating parameters. Experiments were performed at operating conditions corresponding to a gross indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…In contrast to the fast FID data that were presented for the lower-load, partially premixed, Condition I, the temporal evolution of the HC signal differs substantially for different swirl ratios. A previous work on this engine 9 has shown that for a -30°ATDC SOI injection timing, there is the strong likelihood that the injected fuel will not be fully contained within the bowl, and that some fraction of the fuel will enter the piston squish region. In agreement with Colban et al, 13 the initial spike that is seen in the low swirl, Rs = 0.76, data are thought to be associated with HC emissions from fuel trapped in the squish volume and in quench layers along the head and valve surfaces.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In contrast to the fast FID data that were presented for the lower-load, partially premixed, Condition I, the temporal evolution of the HC signal differs substantially for different swirl ratios. A previous work on this engine 9 has shown that for a -30°ATDC SOI injection timing, there is the strong likelihood that the injected fuel will not be fully contained within the bowl, and that some fraction of the fuel will enter the piston squish region. In agreement with Colban et al, 13 the initial spike that is seen in the low swirl, Rs = 0.76, data are thought to be associated with HC emissions from fuel trapped in the squish volume and in quench layers along the head and valve surfaces.…”
Section: Resultsmentioning
confidence: 97%
“…The robustness of the operating strategy in this regard is attributed to the relatively late injection (SOI = –7.5° ATDC (after top dead centre)) timing that ensures that the injected fuel is fully contained within the combustion bowl. 9 With regard to the cycle average HC emissions behaviour, for a fixed oxygen concentration and fuelling, throttling the intake ports in order to increase swirl will reduce the trapped mass and hence increase the global equivalence ratio in-cylinder. It is possible that the increase in HC and CO that is observed when moving from the Rs = 0.76 swirl ratio to the Rs = 1.33 swirl ratio is due to this effect—note that the calculated in-cylinder temperatures are very similar for these two cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The imaging borescope was connected to a Prosilica GC1380 monochrome charge coupled device (CCD) camera to provide spray and combustion imaging within the borescope's field of view (FOV). The specifications of the various optical components used in the experimental set up are given in Table 2; more information is available elsewhere [22,24,25]. The region inside the piston bowl imaged through the borescope at different crank angles is shown in Fig.…”
Section: Experimental Set Upmentioning
confidence: 99%
“…23,24 This splitinjection strategy was also implemented in the intermediate cycles during a combustion mode transition from high-EGR LTC to conventional diesel operation.…”
Section: Effects Of the Load Transient On Cycle-by-cycle Performancementioning
confidence: 99%